2013
DOI: 10.4322/rca.2013.013
|View full text |Cite
|
Sign up to set email alerts
|

Déficit de pressão de vapor d água no ar na distribuição de líquido utilizando um pulverizador hidropneumático

Abstract: RESUMO: A pulverização de agrotóxicos exige conhecimento das condições meteorológicas antes, durante e após as operações no campo. Deste modo, objetivou-se com este trabalho avaliar a influência do déficit de pressão de vapor d'água no ar, nos parâmetros da pulverização produzidos pela ponta de jato cônico vazio JA-2, na cultura da laranja. A pulverização foi realizada utilizando-se um pulverizador hidropneumático. A análise das gotas foi realizada por meio do analisador de partículas a laser e das etiquetas h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Alvarenga et al (2013), working at a pressure of 1,055 kPa and with a JA-2 nozzle, reported that the Figure 1 -Estimates of the volumetric median diameter, the droplet diameter below which is found 10% of the total volume of sprayed liquid, the droplet diameter below which is found 90% of the total volume of sprayed liquid, and the span, with estimates of the percentage of spray volume containing droplets smaller than 100 µm, droplets with a diameter from 100 to 200 µm, a diameter from 200 to 300 µm, a diameter from 300 to 400 µm, a diameter from 400 to 500 µm, a diameter from 500 to 600 µm, and droplets greater than 600 µm, for the VPD air and working pressure. (a) VMD; (b) Dv 10 ; (c) Dv 90 ; (d) span; (e) %V < 100; (f) 100 < %V <200; (g) 200 <%V < 300; (h) 300 <%V < 400; (i) 400 < %V < 500; (j) 500 < %V <600; (k) % >600 ** Significant at 1% probability by t-test.…”
Section: Resultsmentioning
confidence: 99%
“…Alvarenga et al (2013), working at a pressure of 1,055 kPa and with a JA-2 nozzle, reported that the Figure 1 -Estimates of the volumetric median diameter, the droplet diameter below which is found 10% of the total volume of sprayed liquid, the droplet diameter below which is found 90% of the total volume of sprayed liquid, and the span, with estimates of the percentage of spray volume containing droplets smaller than 100 µm, droplets with a diameter from 100 to 200 µm, a diameter from 200 to 300 µm, a diameter from 300 to 400 µm, a diameter from 400 to 500 µm, a diameter from 500 to 600 µm, and droplets greater than 600 µm, for the VPD air and working pressure. (a) VMD; (b) Dv 10 ; (c) Dv 90 ; (d) span; (e) %V < 100; (f) 100 < %V <200; (g) 200 <%V < 300; (h) 300 <%V < 400; (i) 400 < %V < 500; (j) 500 < %V <600; (k) % >600 ** Significant at 1% probability by t-test.…”
Section: Resultsmentioning
confidence: 99%
“…Um fator essencial para estimar-se a taxa de aplicação são as diferentes fases fenológicas de cada planta a ser controlada (AGOSTINETO, 2015). À medida que o volume da copa das plantas altera-se, é recomendado o ajuste do volume de calda para melhorar a qualidade da pulverização (ALVARENGA et al, 2013).…”
Section: Introductionunclassified